The growing burden of non-communicable disease among persons living with HIV in Zimbabwe - Smit,M; Olney,J; Ford,NP; Vitoria,M; Gregson,S; Vassall,A; Hallett,TB (AIDS, 2018)
Objectives:We aim to characterize the future noncommunicable disease (NCD)burden in Zimbabwe to identify future health system priorities.Methods:We developed an individual-based multidisease model for Zimbabwe,simulating births, deaths, infection with HIV and progression and key NCD [asthma,chronic kidney disease (CKD), depression, diabetes, hypertension, stroke, breast,cervical, colorectal, liver, oesophageal, prostate and all other cancers]. The modelwas parameterized using national and regional surveillance and epidemiological data.Demographic and NCD burden projections were generated for 2015 to 2035.Results:The model predicts that mean age of PLHIV will increase from 31 to 45 yearsbetween 2015 and 2035 (compared with 20 –26 in uninfected individuals). Conse-quently, the proportion suffering from at least one key NCD in 2035 will increase by26% in PLHIV and 6% in uninfected. Adult PLHIV will be twice as likely to suffer from atleast one key NCD in 2035 compared with uninfected adults; with 15.2% of all keyNCDs diagnosed in adult PLHIV, whereas contributing only 5% of the Zimbabweanpopulation. The most prevalent NCDs will be hypertension, CKD, depression andcancers. This demographic and disease shift in PLHIV is mainly because of reductions inincidence and the success of ART scale-up leading to longer life expectancy, and to alesser extent, the cumulative exposure to HIV and ART.Conclusion:NCD services will need to be expanded in Zimbabwe. They will need tobe integrated into HIV care programmes, although the growing NCD burden amongstuninfected individuals presenting opportunities for additional services developedwithin HIV care to benefit HIV-negative persons.